Strategy of the North Sumatra Province One Stop Integrated Investment and Licensing Service (DPMPPTSP) in Increasing Investment in North Sumatra - Putri, Icha Ferina; Marliyah, Marliyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
In order to increase regional income and public welfare, the North Sumatra Provincial Government through the One Stop Integrated Investment and Licensing Service (DPMPPTSP) of North Sumatra Province seeks to increase investment and investment as a form of helping the performance of the North Sumatra Government. The purpose of this study is that the One Stop Integrated Investment and Licensing Service (DPMPPTSP) of North Sumatra Province can increase investment through an effective strategy. If the strategy is formulated correctly, then the North Sumatra Province One Stop Integrated Investment and Licensing Service (DPMPPTSP) will succeed in increasing investment and the standard of living of the people in North Sumatra. The type of research used is descriptive qualitative research which is used to examine the condition of natural objects where the researcher is the key instrument that emphasizes meaning rather than generalization (Sugiyono 2015:112). The data collection technique is done inductively (drawing conclusions based on special conditions to be treated in general). The results of the study show that there are six specific strategies applied by the DPMPPTSP of North Sumatra Province in increasing investment in North Sumatra, namely improving the quality of licensing services, compiling investment policy regulations in providing investment facilities and facilities, improving the management of public complaints, updating data on investment potential and business opportunities. North Sumatra based on the application system, improving the quality of supervision of the implementation of investment, and formulating strategies and increasing the promotion of more innovative investment.